2009
DOI: 10.4076/1757-1626-2-8766
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune thyroid disease with myasthenia gravis in a 28-year-old male: a case report

Abstract: IntroductionGraves' disease and myasthenia gravis are both auto-immune diseases and the coexistence of these two diseases is rare but well recognized. Myasthenia gravis is more frequent in patients with thyroid disease.Case presentationHere we present a case of 28-year-old male patient having Auto-immune thyroid disease (Graves' disease) with concomitant myasthenia gravis.ConclusionIn conclusion, we report that the coexistence of Myasthenia Gravis with Autoimmune thyroid disease might have prognostic relevance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
3
9
0
3
Order By: Relevance
“…Its clinical expression is variable, ranging from a localized ocular form, to a severe, generalized attack [5,6]. It can be associated with other autoimmune conditions, such autoimmune thyroid disease, especially hyperthyroidism [1][2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its clinical expression is variable, ranging from a localized ocular form, to a severe, generalized attack [5,6]. It can be associated with other autoimmune conditions, such autoimmune thyroid disease, especially hyperthyroidism [1][2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…The principal ocular signs of Graves' disease are exopthalmos and retraction of the superior eyelid. An associated MG should be considered if there is ptosis and/or nystagmus [6,9]. The disproportionate association between thyroid eye disease and MG seems to be related to cross-reactivity against an epitope or autoantigen that is common to the thyroid and the ocular muscles in the context of genetic predisposition [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MG is now regarded as one of the major autoimmune diseases. It was demonstrated that a deficiency in neuromuscu-lar transmission in the disease results from an autoimmune response to postsynaptic AChR, and that the deficiency is occasionally associated with various autoimmune disorders, such as systemic lupus erythematosus, pernicious anemia, HT, and GD [8,9] . Many studies have also shown that AITDs, such as GD and HT, are most frequently associated with MG [5,6,8] .…”
Section: Discussionmentioning
confidence: 99%
“…АИО может сочетаться с другой эндокринной и неэндокринной аутоиммунной патологией [6,7]. В литературе [4,5,8] имеются данные о сочетании миастении и АИО на фоне патологии щитовидной железы. Сведения о сочетании миастении и АИО немногочисленны.…”
Section: наблюдение из практикиunclassified